(3GdMSHIs - (3CHh YHO Gddg eMeO Hf eMeO GdUbWi (B( (3GdSbWi(B) (3GdeGdcjs
(3ChdgG (B:s
(3GdMeO ddg GdPi YdefG eGde fcf fYde hHYO adP dcKQI eGdReJ hYQafi KbGJ GdeSGaQjf hLQJ GdMhGOK ef ecGf Edi ecGf s
(3BNQgG (B:s
(3hSJeGFI ai GdJQHY heGFJG hNeShf hjONd ajgG ef GdHjGV KdGKhf GdcJGH JSYI CQHGY ced HMeO Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3GdfSNI HgG MhGTs
(3HBNQg ahGFOs
(3HChdg agQSs
(3YdjgG hba s
(3HgG fXGe GdJYbjHI s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdSjGSI hGdGLJeGYs